The bank of Japan’s intervention in exchange-traded funds as an effective monetary policy tool - Pretorius, Ramon (Graduate School of Business (GSB), 2018)
Since the end of October 2010, the Bank of Japan has been pursuing a new Asset Purchase Programme, which includes, among other things, direct intervention in the domestic stock market through the purchase of exchange-traded funds. This research study evaluated the impact of the Bank of Japan’s exchange-traded fund purchase programme on market returns using an event study methodology. An investigation into a sample of 33 intervention events in the Nikkei 400 exchangetraded fund and 303 intervention events in the Nikkei 225 exchange-traded fund, found that the average abnormal one-day return is -1.36% for the Nikkei 400 exchange-traded fund and -1.39% for the Nikkei 225 exchange-traded fund, while the average abnormal five-day return is -0.63% and -1.11% for each exchange-traded fund respectively. Due to the high volatility, statistically the returns are indistinguishable from zero. However, this study presents evidence that the Bank of Japan intervenes predominantly during large decreases in the market. Hence, there is suggestive evidence that the Bank of Japan’s policy is effective at reducing market losses, but is not extensive enough to significantly increase returns.